The Endogenous Determination of Time Preference - Becker, G. S.; Mulligan, C. B. (Quarterly Journal of Economics, 1997)
We model a consumer's efforts to reduce the discount on future utilities. Our analysis shows how wealth, mortality, addictions, uncertainty, and other variables affect the degree of time preference. In addition to working out many implications of the model, we discuss evidence on consumption, savings, equilibrium, and the dynamics of inequality. We claim that most ofthat evidence is consistent with the predictions of our approach.